The anti-inflammatory sesquiterpene lactone parthenolide suppresses IL-4 gene expression in peripheral blood T cells - Li-Weber, Min; Krammer, Peter H. (European journal of immunology, 2002)
Sesquiterpene lactones (SL) derived from Mexican India medicinal plants and parthenolide, the major SL from European feverfew, have raised considerable interest because of their anti-inflammatory and complex pharmacological action. Interleukin-4 (IL-4) is a key cytokine that influences the development of T helper 2 cells and plays an important role in the pathogenesis of allergic diseases. We show here that the anti-inflammatory parthenolide suppresses IL-4 expression at the mRNA and the protein levels in a dose-dependent manner. We demonstrate that parthenolide blocks NF-κB binding to two important IL-4 promoter regulatory elements and suppresses promoter activity upon T cell activation. Differences regarding the effects of parthenolide on expression levels of IL-4, IL-2 and IFN-γ were observed. Parthenolide (2.5 μM) could completely suppress IL-4 protein levels secreted in anti-CD3/CD28-stimulated peripheral blood T cells from allergic and normal donors.Complete inhibition of IL-2 and IFN-γ requires higher doses of parthenolide. So far, drugs directed against IL-4 expression have not been described. This finding raises the potential to develop parthenolide to treat IL-4-mediated allergic-like inflammation.
Gesehen am 15.04.2021